Development of a LC-MS/MS methodology for the monitoring of the antichagasic drug benznidazole in human urine samples - Cerutti, Estela Soledad (2014)
Monitoring the drug benznidazole in biological fluids is a powerful tool for clinical diagnostic and pharmacological studies in chagasic patients. However, research in this concern needs to be done. The accurate quantitation of this drug in complex matrices represents a highly challenging task complicated by the absence of sensitive analytical methods. It follows that sample processing strategies, preparation/cleanup procedures, and chromatographic/ionization/detection parameters, were evaluated for method optimization. The summation of this work generated a rapid, selective, sensitive methodology based on reversed-phase chromatography–tandem mass spectrometry for the analysis of benznidazole in urine samples. To the best of our knowledge, this is a first report of a LC–MS/MS platform employed for this application. Matrix effect was determined; a 90% of signal suppression was observed. The limits of detection and quantification were 0.75 and 4.85 μg L−1; respectively. The latter allowed the method׳s application to the detection of benznidazole in clinical studies and pharmacological monitoring analysis.